Modulation of Plasma Fibrinogen Levels by Ciprofibrate and Gemfibrozil in Primary Hyperlipidaemia - de Maat, M P M; Knipscheer, H C; Kastelein, J J P; Kluft, C (Thrombosis and Haemostasis, 1997)
An elevated plasma fibrinogen level is increasingly accepted as an independent risk indicator of cardiovascular disease. This has enhanced the interest in identifying agents that can normalize elevated plasma fibrinogen levels. One group of agents with this capacity are the fibric acid derivatives, e.g. ciprofibrate and gemfibrozil.We studied fibrinogen levels after 12 weeks of treatment with ciprofibrate (n = 48) and gemfibrozil (n = 51) in hypercholesterolemic patients. The correlation of the decrease in fibrinogen with lipid lowering and the contribution of the acute phase and genetic polymorphisms to this decrease were also evaluated.After 12 weeks of treatment, the fibrinogen levels were significantly decreased (p<0.0005) with both drugs, although the decrease in the ciprofibrate group (mean 3.4 g/1 pre-treatment to 2.4 g/1 after 12 weeks) was larger than in the gemfibrozil group (mean 3.4 g/1 to 3.0 g/1.). The lipid lowering effect was comparable for the two drugs but there was no correlation for either ciprofibrate or gemfibrozil between the lipid lowering and the magnitude or the velocity of the fibrinogen lowering effect. An attenuation of the major regulatory mechanism of plasma fibrinogen levels, the acute phase reaction, was invoked as the underlying mechanism. However, pre-treatment C-reactive protein levels were not increased and did not change after treatment. Moreover, no effects of the polymorphisms of the fibrinogen β-gene on the decrease of the plasma fibrinogen levels were observed. This suggests that a new, as yet unknown, mechanism is involved in fibrinogen lowering by fibrates.